Speech and Language Impairments in Autism: Insights from Behavior and Neuroimaging - Mody, PhD, Maria; Belliveau, PhD, John W. (North American Journal of Medicine and Science, 2012)
A failure to develop language is one of the earliest signs of autism. The ability to identify the neural signature of this deficit in very young children has become increasingly important, given that the presence of speech before five years of age is the strongest predictor for better outcomes in autism. This review consolidates what is known about verbal and preverbal precursors of language development as a framework for examining behavioral and brain anomalies related to speech and language in autism spectrum disorders. Relating the disruptions in the speech network to the social deficits observed will provide promising targets for behavioral and pharmacological interventions in ASD.